2015
DOI: 10.1002/2015gl065925
|View full text |Cite
|
Sign up to set email alerts
|

The importance of Harmattan surges for the emission of North African dust aerosol

Abstract: Dust aerosol is important in the Earth system, but the relative impact of meteorological mechanisms on North African dust emission remains unclear. This study presents the first climatology of dust emission amounts associated with Harmattan surges (HSs), characterized by postfrontal strengthening of near‐surface winds. A new automated identification uses their strong isallobaric winds as an indicator for HSs in 32 years of ERA‐Interim reanalysis. Their impact on dust aerosol emission is estimated by combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 65 publications
(91 reference statements)
0
23
0
Order By: Relevance
“…During the northern hemisphere cold season (November to April), the North African climate is influenced by the northeasterly trade winds called the Harmattan, which is the result of meridional pressure gradients at the synoptic scale across the Saharan desert and can be viewed as part of the meridional circulation (Burton et al, ). Fiedler et al () showed that synoptic scale cold air advection over North Africa causes increased intensity and fluctuations in this system, that is, the Harmattan surges. Regionally, the importance of the study of the Harmattan wind system has been increasing since this system advects a significant amount of mineral dust equatorward, causing negative impacts on visibility, agriculture, and human health (e.g., causes meningitis) (Burton et al, ; Kalu, ; Pérez García‐Pando et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…During the northern hemisphere cold season (November to April), the North African climate is influenced by the northeasterly trade winds called the Harmattan, which is the result of meridional pressure gradients at the synoptic scale across the Saharan desert and can be viewed as part of the meridional circulation (Burton et al, ). Fiedler et al () showed that synoptic scale cold air advection over North Africa causes increased intensity and fluctuations in this system, that is, the Harmattan surges. Regionally, the importance of the study of the Harmattan wind system has been increasing since this system advects a significant amount of mineral dust equatorward, causing negative impacts on visibility, agriculture, and human health (e.g., causes meningitis) (Burton et al, ; Kalu, ; Pérez García‐Pando et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dust can serve as ice nuclei and affect the formation, lifetime, and characteristic of clouds (e.g., Levin et al, 1996;Rosenfield et al, 1997;Wurzler et al, 2000;Nakajima et al, 2001;Bangert et al, 2012), perturbing the hydrological cycle. Iron-and phosphorus-enriched dust is also an important nutrient for the marine and terrestrial ecosystems and thus interacts with the ocean and land biogeochemical cycles (e.g., Fung et al, 2000;Jickells et al, 2005;Shao et al, 2011;Bristow et al, 2010;Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Northeasterly/easterly low-level trade winds over northern Africa, commonly referred to as Harmattan winds, prevail in the area and therefore normal conditions do not favor the poleward advection to the Mediterranean and Europe. The intensity of these winds can be modulated by cold air outbreaks in Western Europe resulting in stronger dust transport over the Tropical North Atlantic (e.g., Fiedler et al, 2015;Schepanski et al, 2017). As a consequence, intense dust export has a highly episodic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a considerable effort has been made in recent years to identify the dust source areas and the main processes leading to dust entrainment in North Africa (e.g., Knippertz & Todd, 2012, and references therein;Schepanski et al, 2007Schepanski et al, , 2009Fiedler et al, 2014Fiedler et al, , 2015Pokharel et al, 2017). Over the drylands of North Africa, dust is mainly mobilized in deflatable areas by low-level jets, synoptic scale circulations, convective features and downslope winds.…”
Section: Introductionmentioning
confidence: 99%